Unravelling the Novel Effects of Three Volatile Compounds in Preventing Fibril Formation of Disease Related Tau and α-Synuclein Proteins- Towards Identifying Candidate Aromatic Substances for Treating Neurodegenerative Diseases - Moeini, Zahra; Seraj, Zahra; Zohoorian Abootorabi, Toktam; Ashrafi-Kooshk, Mohammadreza; Riazi, Gholamhossein; Saboury, Ali Akbar; Seyedarabi, Arefeh (Frontiers in Pharmacology, 2022)
Background: The aggregation of tau and α-synuclein into fibrillary assemblies in nerve cells are the molecular hallmarks of Alzheimer’s and Parkinson’s diseases, respectively. In our previous studies we investigated the anti-amyloidogenic effects of three different aroma producing (volatile) compounds including cinnamaldehyde, phenyl ethyl alcohol and TEMED, on the fibrillation process of HEWL, as a model protein. Our previous results showed that, while TEMED was able to completely stop the process of fibril formation, cinnamaldehyde and phenyl ethyl alcohol gave rise to oligomeric/protofibrillar forms and were involved in the entrapment of intermediate species of HEWL. In this study, we investigated the anti-amyloidogenic effect from the same three volatile compounds on recombinantly produced tau and α-synuclein protein. Methods: Thioflavin T fluorescence assay, Circular Dichroism, SDS-PAGE and/Native-PAGE, Dynamic Light Scattering, and Atomic Force Microscopy were used, where necessary, to further our understanding of the inhibitory effects of the three volatile compounds on the fibril formation of tau and α-synuclein protein and allow a comparison with previous data obtained for HEWL. Results: Our results revealed that contrary to the results obtained for HEWL (a globular protein), the volatile compound TEMED, was no longer able to prevent fibril formation in either of the natively unstructured tau or α-synuclein protein, and instead, cinnamaldehye and phenyl ethyl alcohol, in particular, had the role of preventing fibril formation of tau or α-synuclein. Conclusions: The results of this study further emphasised on the exclusion of HEWL as a model protein for fibrillation studies and highlighted the importance of studying brain related protein such as tau or α-synuclein, and the need to assess the effects of volatile compounds such as cinnamaldehye and phenyl ethyl alcohol as potential substances for the treatment of neurodegenerative diseases.